Ag2Cu2O3- a catalyst template material for selective electroreduction of CO to C(2+)products - Marti, Nemanja; Reller, Christian; Macauley, Chandra; Löffler, Mario; Reichert, Andreas; Reichbauer, Thomas; Vetter, Kim-Marie; Schmid, Bernhard; McLaughlin, David; Leidinger, Paul; Reinisch, David; Vogl, Christoph; et al. (Energy and Environmental Science, 2020)
Although recent years have brought significant progress within the field of electrochemical conversion of CO(2)and CO to value-added chemicals, many more challenges need to be overcome for this technology to be implemented on an industrial level. Rational design of catalyst materials that would enable selective production of desired products at industrially relevant current densities (>200 mA cm(-2)) is most certainly one of them. Here, we introduce Ag2Cu2O3, a mixed-metal oxide, as a starting template material for efficient electroreduction of CO to C(2+)products. By combining results from electrochemical real-time mass spectrometry (EC-RTMS), XRD and XPS we confirmed the template nature of Ag(2)Cu(2)O(3)andin situformation of a fully reduced CuAg bimetallic material during the first minutes of electrolysis. Electrochemical screening of the catalyst revealed significantly varying product distributions when CO2(CO2RR) and CO (CORR) where used as feed gases. During CORR, a faradaic efficiency close to 92% towards C(2+)products at 600 mA cm(-2)was achieved. On the other hand, during CO2RR, CO was found to be the main product under all tested current densities, reaching a maximum faradaic efficiency of 68%. XPS valence band spectra of the bimetallic surface originating from Ag(2)Cu(2)O(3)showed that its d-band electronic structure is noticeably different compared to metallic Ag and Cu, a finding we link to the observed product distributions. Finally, additional microscopy characterization techniques were used to investigate the observed surface reconstruction of the catalyst material under reaction conditions.
CRIS-Team WoS Importer:2020-10-02

A versatile cryo-transfer system, connecting cryogenic focused ion beam sample preparation to atom probe microscopy - Macauley, Chandra; Heller, Martina; Rausch, Alexander; Kümmel, Frank; Felfer, Peter (PLoS ONE, 2021)
Atom probe tomography (APT) is a powerful technique to obtain 3D chemical and structural information, however the ‘standard’ atom probe experimental workflow involves transfer of specimens at ambient conditions. The ability to transfer air- or thermally-sensitive samples between instruments while maintaining environmental control is critical to prevent chemical or morphological changes prior to analysis for a variety of interesting sample materials. In this article, we describe a versatile transfer system that enables cryogenic- or room-temperature transfer of specimens in vacuum or atmospheric conditions between sample preparation stations, a focused ion beam system (Zeiss Crossbeam 540) and a widely used commercial atom probe system (CAMECA LEAP 4000X HR). As an example for the use of this transfer system, we present atom probe data of gallium- (Ga)-free grain boundaries in an aluminum (Al) alloy specimen prepared with a Ga-based FIB.
CRIS-Team Scopus Importer:2021-02-12

Between defects and inclusions: The fate of tellurium in pyrite - Börner, Frederik; Keith, Manuel; Fougerouse, Denis; Macauley, Chandra; Felfer, Peter; Yokosawa, Tadahiro; Apeleo Zubiri, Benjamin; Spiecker, Erdmann (Chemical Geology, 2023)
Tellurium (Te) is a critical commodity, essential for renewable energy technologies and other high-tech applications. Most Te is currently recovered from anode slimes, i.e., waste arising from copper refining. Rising demand and the key role for the green transition make the diversification and extension of the Te supply important. However, the nature of Te incorporation into ores is still poorly understood and hinders their economic potential. Here, we investigate the distribution of Te in pyrite from a high-grade Au-Ag-Te epithermal-type ore, where pyrite is already processed for ‘invisible’ Au, to inform metallurgical extraction methods, and secure future Te supply. Current models of Te incorporation into pyrite suggest a solid-solution limit in relation to As, similar as for ‘invisible’ Au. In this study, we identified three distinct modes of Te incorporation in pyrite, which challenge previous solubility models: (1) Te solid-solution, at concentrations (up to 285 ppma) that significantly exceed the previously suggested solubility limit. (2) Nano-telluride inclusions along cracks that formed by intra-grain remobilization. (3) Crystal defects, enriched in Te through pipe diffusion hosting up to 0.5 at. % Te. Our results therefore provide new fundamental insights into the chemical and structural coordination of Te in pyrite, which may guide future efforts for its direct recovery.
CRIS-Team Scopus Importer:2023-09-01
Keywords: Atom probe tomography (APT); Defects; Inclusions; Low sulfidation epithermal; Pyrite; Solid solution; Tellurium (Te); Vatukoula

Between defects and inclusions: The fate of tellurium in pyrite - Börner, Frederik; Keith, Manuel; Fougerouse, Denis; Macauley, Chandra; Felfer, Peter; Yokosawa, Tadahiro; Apeleo Zubiri, Benjamin; Spiecker, Erdmann (Chemical Geology, 2023)
Tellurium (Te) is a critical commodity, essential for renewable energy technologies and other high-tech applications. Most Te is currently recovered from anode slimes, i.e., waste arising from copper refining. Rising demand and the key role for the green transition make the diversification and extension of the Te supply important. However, the nature of Te incorporation into ores is still poorly understood and hinders their economic potential. Here, we investigate the distribution of Te in pyrite from a high-grade Au-Ag-Te epithermal-type ore, where pyrite is already processed for ‘invisible’ Au, to inform metallurgical extraction methods, and secure future Te supply. Current models of Te incorporation into pyrite suggest a solid-solution limit in relation to As, similar as for ‘invisible’ Au. In this study, we identified three distinct modes of Te incorporation in pyrite, which challenge previous solubility models: (1) Te solid-solution, at concentrations (up to 285 ppma) that significantly exceed the previously suggested solubility limit. (2) Nano-telluride inclusions along cracks that formed by intra-grain remobilization. (3) Crystal defects, enriched in Te through pipe diffusion hosting up to 0.5 at. % Te. Our results therefore provide new fundamental insights into the chemical and structural coordination of Te in pyrite, which may guide future efforts for its direct recovery.<br
Keywords: Pyrite; Tellurium (Te); Atom probe tomography (APT); Low sulfidation epithermal; Solid solution; Inclusions; Defects; Vatukoula

Cumulate olivine: A novel host for heavy rare earth element mineralization - Brandt, Sönke; Faßbender, Marc Lorin; Klemd, Reiner; Macauley, Chandra; Felfer, Peter; Haase, Karsten (Geology, 2020)

Fracture resistance of yttria stabilized zirconia manufactured from stabilizer-coated nanopowder by micro cantilever bending tests - Giese, Sven; Kern, F.; Macauley, Chandra; Neumeier, Steffen; Göken, Mathias (Journal of the European Ceramic Society, 2019)
Yttria stabilized tetragonal zirconia polycrystal (Y-TZP)owes its high toughness to transformation toughening, a mechanism that requires the development of a process zone. It is important to measure if and to what extent the size of components can be reduced. In this study, tests were carried out using focused ion beam or picosecond milled pre-notched, 3 mol percent Y 2 O 3 (3Y-)TZP micro-cantilever (10–250 μm)beams. The tests show clearly that the maximum fracture resistance is size dependent and the plateau toughness was not reached in any of the small-scale samples. A correlation between transformability of the tetragonal phase and the measured fracture resistance became visible only for the largest micro cantilever but did not reach the values measured in macroscopic samples. Based on these results, it is not advantageous to use very tough zirconia materials in components with dimensions smaller than ∼0.25 mm, as the high toughness is not fully realized.
CRIS-Team Scopus Importer:2019-05-14
Keywords: Ceramic; Fracture toughness; Micro cantilever; Small scale; TZP

Indium and antimony distribution in a sphalerite from the “burgstaetter gangzug” of the upper harz mountains pb-zn mineralization - Schirmer, Thomas; Ließmann, Wilfried; Macauley, Chandra; Felfer, Peter (Minerals, 2020)
The sphalerite from the Burgstaetter Gangzug, a vein system of the Upper Harz Mountain nearby the town of Clausthal-Zellerfeld, exhibits a very interesting and partly complementary incorporation pattern of Cu, In and Sb, which has not yet been reported for natural sphalerite. A sphalerite specimen was characterized with electron probe micro-analysis (EPMA) and atom probe tomography (APT). Based on the EPMA results and a multilinear regression, a relation expressed as Cu = 0.98In + 1.81Sb + 0.03 can be calculated to describe the correlation between the elements. This indicates, that the incorporation mechanisms of In and Sb in the structure differ substantially. Indium is incorporated with the ratio Cu:In = 1:1 like in roquesite (CuInS2), supporting the coupled substitution mechanism 2Zn2+ → Cu+ + In3+. In contrast, Sb is incorporated with a ratio of Cu:Sb = 1.81:1. APT, which has a much higher spatial resolution indicates a ratio of Cu:Sb = 2.28:1 in the entire captured volume, which is similar to the ratio calculated by EPMA, yet with inhomogeneities at the nanometer-scale. Analysis of the solute distribution shows two distinct sizes of clusters that are rich in Cu, Sb and Ag.
CRIS-Team Scopus Importer:2020-09-18
Keywords: Antimony; APT; Element distribution; EPMA; Indium; Pb-Zn-mineralization; Sphalerite; Upper Harz Mountains

Influence of Ta on the oxidation resistance of WB2−z coatings - Fuger, C.; Schwartz, B.; Wojcik, T.; Moraes, V.; Weiss, M.; Limbeck, A.; Macauley, Chandra; Hunold, O.; Polcik, P.; Primetzhofer, D.; Felfer, Peter; Mayrhofer, P. H.; et al. (Journal of Alloys and Compounds, 2020)
Ternary W1−xTaxB2−z is a promising protective coating material possessing enhanced ductile character and phase stability compared to closely related binaries. Here, the oxidation resistance of W1−xTaxB2−z thin films was experimentally investigated at temperatures up to 700 °C. Ta alloying in sputter deposited WB2−z coatings led to decelerated oxide scale growth and a changed growth mode from paralinear to a more linear (but retarded) behavior with increasing Ta content. The corresponding rate constants decrease from kp* = 6.3 ⋅ 10−4 µm2/s for WB2−z, to kp* = 1.1 ⋅ 10−4 µm2/s for W0.66Ta0.34B2−z as well as kl = 2.6 ⋅ 10−5 µm/s for TaB2−z, underlined by decreasing scale thicknesses ranging from 1170 nm (WB2−z), over 610 nm (W0.66Ta0.34B2−z) to 320 nm (TaB2−z) after 10 min at 700 °C. Dense and adherent scales exhibit an increased tantalum content (columnar oxides), which suppresses the volatile character of tungsten-rich as well as boron oxides, hence being a key-factor for enhanced oxidation resistance. Thus, adding Ta (in the range of x = 0.2–0.3) to α-structured WB2−z does not only positively influence the ductile character and thermal stability but also drastically increases the oxidation resistance.
CRIS-Team Scopus Importer:2020-12-25
Keywords: Diborides; Oxidation resistance; Scale growth; Transition metal diborides

Paramelaconite-Enriched Copper-Based Material as an Efficient and Robust Catalyst for Electrochemical Carbon Dioxide Reduction - Martić, Nemanja; Reller, Christian; Macauley, Chandra; Löffler, Mario; Schmid, Bernhard; Reinisch, David; Volkova, Elena; Maltenberger, Anna; Rucki, Andreas; Mayrhofer, Karl; Schmid, Günter (Advanced Energy Materials, 2019)
A copper-oxide-based catalyst enriched with paramelaconite (Cu4O3) is presented and investigated as an electrocatalyst for facilitating electroreduction of CO2 to ethylene and other hydrocarbons. Cu4O3 is a member of the copper-oxide family and possesses an intriguing mixed-valance nature, incorporating an equal number of Cu+ and Cu2+ ions in its crystal structure. The material is synthesized using a solvothermal synthesis route and its structure is confirmed via powder X-ray diffraction, transmission electron microscope based selected area electron diffraction, and X-ray photoelectron spectroscopy. A flow reactor equipped with a gas diffusion electrode is utilized to test a copper-based catalyst enriched with the Cu4O3 phase under CO2 reduction conditions. The Cu4O3-rich catalyst (PrC) shows a Faradaic efficiency for ethylene over 40% at 400 mA cm−2. At −0.64 versus reversible hydrogen electrode, the highest C2+/C1 product ratio of 4.8 is achieved, with C2+ Faradaic efficiency over 61%. Additionally, the catalyst exhibits a stable performance for 24 h at a constant current density of 200 mA cm−2.
CRIS-Team Scopus Importer:2019-07-09
Keywords: carbon dioxide electroreduction; Cu; gas diffusion electrodes; mixed-valence; paramelaconite

Phase equilibria in the ZrO2-YO1.5-TaO2.5 system at 1250 degrees C - Macauley, Chandra; Fernandez, Abel N.; Van Sluytman, Jason S.; Levi, Carlos G. (Journal of the European Ceramic Society, 2018)
The phase relationships in the ZrO2-YO1.5-TaO2.5 (ZYTO) system at 1250 degrees C-a temperature of interest for thermal barrier coatings applications-were investigated using precursor-derived powders. The system is bisected by a quasi-binary joining the tetragonal (t) ZrO2 and monoclinic (M') YTaO4 solid solutions. The mutual solubility limits for these phases differ significantly depending on whether the third phase in equilibrium with t and M' is fluorite or the orthorhombic (O) Zr6Ta2O17. More importantly, the tetragonal phase in equilibrium with fluorite is non-transformable to the monoclinic form upon cooling, whereas that in equilibrium with O, which has lower stabilizer content, is transformable. The behavior contrasts with that previously observed for the equilibrium at 1500 degrees C, wherein the t phase on both sides of the quasi-binary is non-transformable. The fluorite solid solution extends from the ZrO2-YO1.5 binary to the YO1.5-TaO2.5 binary at 1250 degrees C, as previously shown for 1500 degrees C.
Keywords: Thermal barrier coatings; Zirconia; Yttria; Tantala; Phase equilibria

Thermochemistry and phase stability of the polymorphs of yttrium tantalate, YTaO4 - Lepple, Maren; Ushakov, Sergey V.; Lilova, Kristina; Macauley, Chandra; Fernandez, Abel N.; Levi, Carlos G.; Navrotsky, Alexandra (Journal of the European Ceramic Society, 2020)
Thermodynamic parameters of the three fergusonite-related polymorphs M’, M and T of YTaO4 and their phase stabilities were investigated experimentally. The debate on the relative stability of the M and M’ phases was resolved, and it was shown that the compound does not transform to a cubic polymorph prior to melting. The enthalpies of formation of M and M’ were determined using high temperature oxide melt solution calorimetry, and the heat capacities and heat contents were measured. The enthalpy of the M’ to T phase transition was measured by differential thermal analysis. The stability of the T phase up to its melting at 2090 °C was demonstrated using high temperature X-ray diffraction and thermal analysis. Its enthalpy of fusion was determined using drop-and-catch calorimetry. The thermodynamic properties of YTaO4 assessed in this study enable the thermodynamic modeling of its polymorphs and related materials systems of technological importance.
CRIS-Team Scopus Importer:2020-11-06
Keywords: Calorimetry; Oxide materials; Synchrotron radiation; Thermal analysis; Thermodynamic properties; YTaO; Yttrium tantalate